Column Base Plate Design Table - Chhabra, Surendra J. (Engineering Journal, 1994)
The column base plate design procedure given in AISC ASD Ninth Edition manual1 differs considerably from the Eighth Edition manual. Additionally, the procedure contained in the first printing of the Ninth Edition manual has been refined in the later printings of the manual to incorporate improvements proposed by Thornton. These changes result in lighter base plates under certain conditions of loading and base plate geometry. The purpose of this paper is to provide a design table that includes AISC Ninth as well as Eighth Edition base plates, and to compare the two designs. The basis for the design method contained in the AISC manual has been discussed in detail by others, and will not be repeated here.